UJI AKTIVITAS INFLAMASI EKSTRAK ETANOL DAUN KELOR (Moringa oleifera L.) TERHADAP TIKUS PUTIH JANTAN (Galur wistar) - Delisma Simorangkir; Jenti Hutagalung; Palas Tarigan (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2020)
Background: Inflammation is a protective response of the body from the injury of the cell. Edema is one of the inflammation symptoms. Drumstick (Moringa oleifera L.) contains flavonoid a major of a bioactive constituent. Flavonoids inhibit COX-2 in inflammatory in mice. Objective: This study aims to investigate and to determine the anti-inflammatory activity and its effective dose extract. Method: Experimental. The extract was prepared by maceration method using ethanol 80%. An anti-inflammatory activity test was performed in five different groups. Each group consisted of 5 rats. The 1st group (negative control) was given 0,5% CMC-Na suspension, the 2nd group (positive control) was given diclofenac sodium 2,25 mg/kg BW, the 3rd, 4th, and 5th groups were successively given the drumstick leaf extract as much as 100, 150, and 200 mg/kg BW. Each rat was then induced by 1% carrageenan and tested using the subplantar method. The inflamed paw volume was measured using plestymometer. The measurements were done for 3 hours long with intervals of 30 minutes. The data were statistically analyzed using ANOVA (Analysis of Variance). Results: The results showed that the negative control had a significant difference with the other treatment groups which did not show any anti-inflammatory effect. Conclusion: Extract of a drumstick at a dose of 200 mg/kg BW has a better anti-inflammatory effect than ethanolic of a drumstick at dose of 100, 150 mg/kg BW, but still under sodium diclofenac.